1985
DOI: 10.1002/j.1460-2075.1985.tb03991.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates of influenza virus. Structural elucidation of the individual glycans of the FPV hemagglutinin by two-dimensional 1H n.m.r. and methylation analysis.

Abstract: The structures of the oligosaccharides of the hemagglutinin of fowl plague virus [influenza A/FPV/Rostock/34 (H7N1)] have been elucidated by one‐ and two‐dimensional 1H n.m.r. spectroscopy at 500 MHz and by microscale methylation analysis. N‐Glycosidic oligosaccharides of the oligomannosidic (OM) and of the N‐acetyllactosaminic type have been found, the latter type comprising biantennary structures, without (A) or with (E) bisecting N‐acetylglucosamine, and triantennary (C) structures. Analysis of the tryptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…It has been suggested by Laskey et al (27) that this CD4 interaction site of gp120 may be found in a cleft, hence rendering it relatively antigenically inaccessible . This same tertiary conformation may explain the presence of high chains at these sites as steric accessibility of oligosaccharides is an important factor in processing of high mannose oligosaccharides to complex sugars (28,29). The conservation of this region and the potential glycosylation sites in different isolates of HIV I as well as between HIV I and HIV 2 (30), raises the possibility that these high mannose glycans could provide conserved targets for potential therapeutic agents .…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested by Laskey et al (27) that this CD4 interaction site of gp120 may be found in a cleft, hence rendering it relatively antigenically inaccessible . This same tertiary conformation may explain the presence of high chains at these sites as steric accessibility of oligosaccharides is an important factor in processing of high mannose oligosaccharides to complex sugars (28,29). The conservation of this region and the potential glycosylation sites in different isolates of HIV I as well as between HIV I and HIV 2 (30), raises the possibility that these high mannose glycans could provide conserved targets for potential therapeutic agents .…”
Section: Discussionmentioning
confidence: 97%
“…The failure to observe this crosspeak can be ascribed to the ineffective magnetization transfer in the case of protons sharing a small coupling constant and to the effects of a short transverse relaxation time, T2. Such difficulties were encountered for mannose residues of glycopeptides [24] (and references therein) and galactose residues of glycosphingolipids [25] and discussed at some length in a review article [26]. The distribution of signal intensity among several slightly different components of the heterogeneous sample is a further factor impeding the formation of detectable crosspeaks.…”
Section: H-nmr Spectroscopymentioning
confidence: 99%
“…Both regions carry N-linked oligosaccharides (9), which affect the functional properties of HA (10,11). Among different subtypes of influenza A viruses, there is extensive variation in the glycosylation sites of the head region, whereas the stem oligosaccharides are more conserved and required for fusion activity (11).…”
mentioning
confidence: 99%